Polska literatura dziecięca i młodzieżowa w odbiciu crip theory. Wybrane przykłady - Alicja Fidowicz (Paidia i Literatura, 2020)
Author presents the crip theory and its possibility for interpretation of Polish children’s and youth literature. She is focused on the presentation this theory and its compatibility to Polish culture. In the next part of the paper, author analyses poem To my students (Do moich uczniów) by Jan Twardowski and the novel Pupa (Poczwarka) by Dorota Terakowska, using the crip category.